Analysis of The Effectiveness of Wheat Transfer Machines Using Overall Equipment Effectiveness (OEE) and Root Cause Analysis (RCA) In The Jetty Operation Section of The Jetty and Silo Department At PT. XYZ - Syaker, Abdan; Nugraha, Isna (Heuristic, 2025)
PT XYZ is a wheat flour producer that faces high challenges in the effectiveness of the wheat transfer machine in the Jetty Operation Section. This study aims to analyze machine performance using the Overall Equipment Effectiveness (OEE) and Root Cause Analysis (RCA) methods. The results showed the OEE values of Hartman I, Hartman II, and Neuro machines were 93% each, which is classified as normal according to the Japan Institute of Plant Maintenance, but can still be improved. Measurement of the six big losses identified Reduced Speed Losses as the main factor, 1.93% for Hartman I and Hartman II respectively, and Idle and Minor Stoppages Losses at 1.37%. The final stage using RCA provides improvement suggestions based on human, method, material, machine, and environmental factors. These recommendations are expected to increase machine effectiveness and support smooth production in the Jetty Operation Section.